Answer: t = 6
Step-by-step explanation: First we solve for -9(t-2) and that comes out to be -9t + 18. Then we solve for 4(t-15) which comes out to be 4t - 60. So the new equation we have is -9t + 18 = 4t - 60. In order to solve for t, we need to get t on one side of the problem by itself. To do this we will first add 9t to both sides and it comes out to be 18 = 13t - 60. t is still not by itself so now we add 60 to both sides and that gives us 78 = 13t. t is still not by itself so now we need to divide each side by 13 so that variable t is by itself. When we divide both sides by 13 we get 6 = t.